1995
DOI: 10.1111/j.1476-5381.1995.tb14965.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of the novel neuroprotective agent, lifarizine (RS‐87476), on voltage‐dependent sodium currents in the neuroblastoma cell line, N1E‐115

Abstract: 1 The actions of the neuroprotective agent, lifarizine , on voltage-dependent Na+ currents have been examined in the neuroblastoma cell line, NlE-1 15, using the whole-cell variant of the patch clamp technique. 2 At a holding potential of -80mV, lifarizine reduced the peak Na+ current evoked by a lOms depolarizing step with an IC50 of 1.3pLM. At holding potentials of -100 and -60mV the IC50 concentrations of lifarizine were 7.3pM and 0.3LM, respectively.3 At a holding potential of -100 mV, most channels were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…The most likely explanation for these findings is that lifarizine binds selectively to inactivated sodium channels, since these will predominate both in the membrane preparation and in the depolarized synaptosomal preparation. The lower affinity of [3H]-lifarizine in nondepolarized synaptosomes may be due to a proportion, albeit unknown, of the sodium channels in this preparation being in the resting state, for which lifarizine has very low affinity (McGivern et al, 1995).…”
Section: Solubilization and Reconstitution Studiesmentioning
confidence: 89%
See 1 more Smart Citation
“…The most likely explanation for these findings is that lifarizine binds selectively to inactivated sodium channels, since these will predominate both in the membrane preparation and in the depolarized synaptosomal preparation. The lower affinity of [3H]-lifarizine in nondepolarized synaptosomes may be due to a proportion, albeit unknown, of the sodium channels in this preparation being in the resting state, for which lifarizine has very low affinity (McGivern et al, 1995).…”
Section: Solubilization and Reconstitution Studiesmentioning
confidence: 89%
“…Electrophysiological studies have demonstrated that lifarizine has negligible interaction with the open state of the sodium channel (McGivern et al, 1995). In contrast, [3H]-BTX interacts preferentially with open sodium channels (Catterall, 1980 …”
Section: Solubilization and Reconstitution Studiesmentioning
confidence: 99%
“…In vitro lifarizine has been shown to allosterically interact with the toxin site 2 on sodium channel (IC50 55 nm, inhibition of [3H]-batrachotoxin binding), protects against the toxicity induced by the sodium channel activator, veratridine in chick myocytes (Patmore et al, 1991), and in primary cultures of cortical neurones (May et al, 1995). Lifarizine also potently blocks sodium currents in NIE-115 neuroblastoma cells (Ki 0.2 uM; McGivern et al, 1995).…”
Section: Drugs and Chemicalsmentioning
confidence: 99%
“…Lifarizine allosterically interacts with the toxin site 2 on the sodium channel (IC50 55 nM, inhibition of batrachotoxin binding) and potently blocks sodium currents in NlE-115 neuroblastoma cells with an IC50 of 1.3 gM at a holding potential of -80 mV. The potency is modulated by changing the holding potential (7 yM at -100 mV; 0.3 pM at -60 mV) and has been shown to interact predominantly with the inactivated state of the channel (McGivern et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies in man have indicated that the drug is generally well tolerated, and some evidence of benefit in stroke patients has been obtained (Brown et al, 1995a). In terms of proposed mechanism, electrophysiology studies have shown that lifarizine inhibits sodium currents in a voltage-dependent manner (Sheridan et al, 1991;McGivern et al, 1995). This property arises predominantly from an interaction of lifarizine with the inactivated state of the sodium channel, and consistent with this it was found that the potency of lifarizine in inhibiting sodium channels, and in the affinity of [3H]-lifarizine binding to sodium channels, both increased at more depolarized holding potentials MacKinnon et al, 1995).…”
Section: Introductionmentioning
confidence: 99%